Fabrication of a Ag/CNQDs/g-C3N4-PVDF photocatalytic composite membrane with excellent photocatalytic and self-cleaning properties. Issue 5 (October 2022) - Li, Chen; Sun, Tianyi; Yi, Guohui; Zhang, Dashuai; Zhang, Yan; Lin, Xiaoxue; Liu, Jinrui; Shi, Zaifeng; Lin, Qiang
Abstract: A highly efficient visible light-driven photocatalytic membrane composed of Ag/CNQDs/g-C3 N4 and PVDF membranes was successfully prepared by vacuum filter crosslinking. This new type of photocatalytic membrane possessed both excellent photocatalytic degradation performance and photocatalytic self-cleaning properties. The Ag/CNQDs/g-C3 N4 photocatalyst coating amount of 10 mg had the highest photocatalytic degradation of norfloxacin (NOR), and the quasi-first-order kinetic constant ( k ) value was 0.0138 min −1 . Moreover, the mechanism of the photocatalytic reaction was also discussed. In addition, bovine serum albumin (BSA) as the simulated pollutant was applied to evaluate the self-cleaning property of the Ag/CNQDs/g-C3 N4 -PVDF composite membrane. After contamination with BSA, the water flux of the composite membrane decreased from 3880 L (m 2 h) −1 to 800 L (m 2 h) −1 . Then, the maximum pure water flux of the Ag/CNQDs/g-C3 N4 -PVDF photocatalytic composite membrane recovered 87% (3360 L (m 2 h) −1 ) within 90 min of visible light irradiation, indicating that the Ag/CNQDs/g-C3 N4 -PVDF photocatalytic composite membrane had excellent self-cleaning properties. Highlights: The Ag/CNQDs/g-C3 N4 -PVDF was assembled by vacuum filtration-crosslinking method. The Ag/CNQDs/g-C3 N4 -PVDF membrane exhibited both excellent separation performance and photocatalytic self-cleaning properties. The mechanism of photocatalytic degradation of norfloxacin was proposed. The Rr gradually replaced Rir as the main factor affecting membrane fouling under visible light irradiation.